Results of tympanoplasty in reference to the condition of middle ear mucosa and edge of perforation in safe chronic otitis media - Mili, Mohan Kumar; Hoque, Sultan Rezaul; Sarmah, Monikuntal; Phookan, Jyotirmoy (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Chronic suppurative otitis media (CSOM) is an important and a highly prevalent disease of the middle ear and poses serious health problem worldwide especially in developing countries where large percentage of the population lack specialized medical care, suffer from malnutrition and live in poor hygienic environmental conditions. Aim of the study was to study the outcome of tympanoplasty in the light of character of edge of perforation and middle ear mucosa condition. Methods: This prospective study was conducted in 39 patients who underwent tympanoplasty in the department of ENT and head and neck surgery, Assam medical college and hospital, Dibrugarh between 1st June 2019 to 31st May 2020. Rim of perforated tympanic membrane and middle ear mucosa were sent for HPE. Three post-operatives follow up were done and surgical success was measured in terms of graft uptake and improvement in hearing. Results: Out of 39 cases, successful graft uptake was seen in 33 (84.62%) cases. Extension of migration of squamous epithelium in the undersurface of tympanic membrane was found in all 6 cases (3 had complete epidermosis while 3 had partial). All the six graft failure cases had diseased middle ear mucosa, mostly infected hypertrophied mucosa and tympanosclerosis with infiltration of chronic inflammatory cells and 1 patient had keratosis flakes with vascular stroma. Conclusions: Hypertrophic changes with inflammation of middle ear mucosa and epidermosis on the medial surface of tympanic membrane was found to have negative influence on the tympanoplasty outcome.